XI National Meeting of Occupational Therapy Lectures: reflecting on the processes of academic development and professional education - Lopes, Roseli Esquerdo; Oliver, Fátima Corrêa; Malfitano, Ana Paula Serrata; Galheigo, Sandra Maria; Almeida, Marta Carvalho de (Revista de Terapia Ocupacional da Universidade de São Paulo, 2008)
This work presents the description and results of the XI National Meeting of Occupational Therapy Lectures that promoted the collective debate on professional education. The meeting took place in September 2008, at the University of São Paulo, having as central theme the enhancement of the processes of academic development and professional education for citizenship and social inclusion. During the event, some matters advanced, as follows: the reflection and definition of future activities for the articulation and integration of undergraduate education with public policies, such as health, social care and education; the updating and proposition of parameters on the main debate on social technologies in the profession; the definition of collective strategies to deal with the main problems in the field of graduate education and research in the area, among other themes. As an outcome of the event is the acknowledgement that the challenge and the need for a collective effort remain as necessary for the accomplishment of the debated propositions and the continuity of the works. This will make it possible the strengthening and consolidation of occupational therapy in the scope of human resources development, in undergraduate and graduate levels. Also, it may contribute to the implementation of social practices which seek the improvement of the life conditions of people with whom occupational therapy intervenes.